Reduction of Excellent Service Strategy in Increasing Customer Loyalty at BPRS Bhakti Sumekar Madya Pamekasan Branch Office - Iqbal Rafiqi; Farhan Hamim (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2023)
Excellent service in the banking world is the key to increasing customer trust, satisfaction, and loyalty. Meanwhile, some employees of PT. BPRS Bhakti Sumekar Madya Pamekasan Branch Office are not yet optimal in implementing Service Excellent in serving its customers, such as not paying enough attention and not being too active when interacting in providing services. In this case, it is contrary to the basic concept of Service Excellent, which includes A6, attitude, attention, action, ability, appearance, and accountability. The aim of this research is to find out more deeply about the implementation of excellent service at the PT. BPRS Bhakti Sumekar Pamekasan intermediate branch office. The methods used are interview, observation, and documentation methods. From this method, researchers then process and analyze it to obtain data or information. The subjects of this research were taken from employees at the PT. BPRS Bhakti Sumekar Madya Pamekasan Branch Office. For the validity of the data, researchers used triangulation between informants. The results of this research are the implementation of excellent service in serving customers, which is applied in all lines to achieve customer satisfaction, such as excellent service provided in the frontliner section, withdrawing money using BBS Mobile, fast and precise service, implementing 3S (smile, greet, salute), excellent service in the form of security, and improving the quality of excellent service personally. Excellent service itself plays an important role in maintaining customer loyalty to the PT. BPRS Bhakti Sumekar Madya Pamekasan Branch. This is proven by the large number of customers it has, including 1446 active customers and 10 thousand 259 third-party fund customers.